The role of responses to self-critical thoughts in the relationship between perfectionism and distress in Finnish Competitive Athletes - Syrykh, Inna (2025)
Competitive sports nowadays require incredible determination, as well as high physical and psychological effort. Athletes experience stress from various sources, such as competitions, clubs, organizations, and personal life. The high demands of the sports environment often contribute to negative outcomes for the mental wellbeing of athletes. Perfectionism has been found as one of the significant predictors of such psychological issues, as anxiety, depression, burnout, eating disorders, and general distress in athletes. Multidimensional model of perfectionism (Stoeber & Otto, 2006) includes perfectionistic strivings, which tend to be more adaptive, and perfectionistic concerns, which are usually viewed as maladaptive. However, the relationship between perfectionism and distress is most likely to be indirect and includes mechanisms that either increase or buffer stress. One of the facets of perfectionistic concerns is excessive self-criticism, which can be responded to with self-compassionate and kind thoughts, or alternatively with rumination and avoidance. These reactions are defined as responses to self-critical thoughts and can be categorized as flexible and inflexible. One of the possible mediators between perfectionism and distress is responses to self-critical thoughts. The thesis aimed to examine whether responses to self-critical thoughts affect the relationship between perfectionistic concerns and distress. Furthermore, it aimed to examine whether there are gender differences in perfectionism, distress, and responses to self-critical thoughts.